The persistence of prairie dogs within urban habitat islands in the Colorado Front Range - Magle, Seth B., author; Crooks, Kevin, advisor; Detling, James K., committee member; Reading, Richard, committee member; Theobald, David, committee member (Colorado State University. Libraries, 2007)
I investigated the ecology of black-tailed prairie dogs in fragmented urban habitat in the Denver, Colorado metropolitan area. My study area consisted of 387 habitat fragments, 54 of which were colonized by prairie dogs. These fragments were highly isolated and surrounded by roads and development, and my studies represent the first studies of prairie dogs in highly urban environments. I evaluate the interactions between urban prairie dogs and vegetation and find that prairie dogs in urban areas tend to be present on sites with high grass coverage, though the grass layer is reduced in the immediate vicinity of the colonies. Prairie dogs interact with vegetation similarly in urban areas and natural habitat, providing evidence that the ecological role of prairie dogs as keystone species may be partly retained in human-dominated landscapes. I provide the first study using mark-resight methodology to evaluate the local population density of prairie dogs, and find it more accurate than traditional methods of burrow counts or visual indices. I observed extremely high densities for prairie dogs in urban settings, probably because of a fence effect where animals are restricted to available habitat due to the difficulty of dispersal in an urban environment. I compare connectivity metrics to determine which have the best predictive power for the occurrence of colonies in this area, and find that complex methods incorporating area of patches and cost-weighted distance surfaces perform best. In general, inclusion of biological information improves the ability of metrics to predict wildlife distribution. This study provides a rare opportunity to compare the performance of connectivity metrics using empirical data on wildlife distribution and will be of benefit to future spatial and landscape analyses. Finally, I evaluate a series of landscape and local variables to determine which have the most importance to the distribution of prairie dogs across our study system. Fragment area and local variables such as litter coverage have the most explanatory power, but all tested metrics had importance to prairie dog occurrence. My results can be used to target potential habitat for prairie dog conservation and to inform future research on wildlife in urban areas.
Keywords: ecology